SUSTAINABLE MARINE TOURISM IN ALOR: A STUDY OF COASTAL COMMUNITIES’ PERCEPTION - Alexander M. A. Khan; Imam Musthofa; Indarwati Aminuddin; Fitri Handayani; Ratna N Kuswara; Imanuel L Wabang; Ajeng Wulandari; Evi Novianti; Ute L. S. Khadijah (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Purpose: This research aims to determine the tourism potential based on the community’s perception of the existing natural resource and determining the management strategies for the tourism area. Research methods: The research method used in this study is the survey method. This research method was divided into two steps, including data collection using the snowball method and data analysis carried out with a descriptive method for the potential of tourism development and qualitative- quantitative approaches based on the perceptions of the local community to determine the development strategy. Results and discussions: The results showed that several natural resources in Alor can be used as a tourist attraction, such as Wai Ulung, Wai Redang, Wai Urita, Wai Bakolang, Munaseli Kingdom, Hiking Baki Old Village, Kenari beach, Sikka Island, Putri Laut Cave, Tomi Leo Cave, Bat Cave, and Octopus Pond. Based on the analysis using the quantitative and qualitative SWOT Matrix, the suitable strategy to be applied in the development of sustainable tourism in Alor is maximize the strength to get all of the opportunity, such as developing tourism activities with fully managed by the local community, promotes safe tourist sites, provides sustainable tourism development field-laboratory for students and academia, and Enhance the community involvement as local tour services providers. Conclusion: Many natural and historical resources in Alor that can be developed as a tourist attraction, and the suitable development strategy is to maximize the strength to get all the opportunity. Keywords: Alor, development strategy, natural resources, sustainable tourism, SWOT analysis, tourism potential